INVERSE PROBLEM OF A STURM-LIOUVILLE OPERATOR WITH NON-SEPARATED BOUNDARY VALUE CONDITIONS AND SYMMETRIC POTENTIAL - Shaldanbayev A.Sh; A.A. Shaldanbayeva; B.A. Shaldanbay (Academic Scientific Journal of Computer Science, 2019)
In this paper we prove a uniqueness theorem, in a single spectrum, for the Sturm-Liouville operator with non-separated boundary value conditions and real continuous and symmetric potential. The research method is different from all known methods, and based on internal symmetry of the operator generated by invariant subspaces.